Current energy recycling technology for agricultural waste in Malaysia - Yow, Hui Ming; Amir, Abdul Razak; Alheemar, Adel Aboulqasim (Penerbit Akademia Baru, 2024)
This article examines the production and use of biomass as a renewable energy source in Malaysia, focusing on the agricultural processing industry. Malaysia produces approximately 168 million tonnes of biomass, including palm oil waste, rice husks, coconut debris, sugar cane waste, urban waste, and forestry waste. The abundance of biomass resources provides a competitive advantage over other renewable energy sources. However, the industry faces restrictions and challenges, such as high disposal costs, high electricity consumption, and related expenses. To address these issues, it is crucial to study the types of biomass available, current technology for biomass energy production (waste-to-energy), and relevant environmental motivations, initiatives, and legislation. This paper analyses the agricultural waste available for energy generation, existing technologies for converting waste into energy, and the role of environmental policies in the agricultural processing business. Energy recycling, which involves utilizing agricultural waste to generate electricity and thermal energy, is proposed as a viable solution. Several technologies are explored, including anaerobic digestion, gasification, incineration/combustion, and pyrolysis, each with advantages and disadvantages. Thermochemical processes are highlighted for their effectiveness, requiring minimal pre-treatment, shorter reaction times, and adaptability to various biomass feedstocks and climatic conditions. The implementation of incentives, initiatives, and policies by the Malaysian government serves as guidelines for the agricultural processing industry to adopt energy recycling practices. By emphasising energy sustainability and promoting green building initiatives, the industry can contribute to a more sustainable and environmentally friendly energy landscape.